국내 개발 신약의 기술개발 소요기간 분석 - 조정연(Jeong-Yeon Cho), 이상원(Sang-Won Lee) (Yaghag-hoi-ji, 2020)
There are more than 30 new drugs developed by Korean companies, but empirical research on the new drugdevelopment process is insufficient. This study aimed to compare the development time for new drugs developed byKorean companies with previous studies on foreign companies. This study defined and analyzed each milestone of thedrug development process through a public data source for new drugs approved from 1999 to 2019. The development timebefore initial human testing was 2.8 years and the time for each clinical development phase were 1.4 year, 2.4 year and3.1 year, respectively. The result was similar with the previous studies in other countries. In addition, as in the case ofprevious research, the development time has increased in recent years. KCI Citation Count: 0